Efficacy of Some Native Botanical Extracts on the Repellency Property Against the Pink Mealy Bug, Maconellicoccus hirsutus (Green) in Mulberry Crop - and V. Bhaskaran2, V. Sathyaseelan1* (Recent Research in Science and Technology, 2010)
Mulberry, Morus alba, (L.) leaves are the predominant food source for Silkworm, Bombyx mori rearing.Â Pink mealy bug infests the mulberry plants and cause Tukra diseases that leads to qualitative loss of leaves.Â Hence a study was carried out to evaluate the efficacy of various indigenous native botanical extracts for their repellency property against pink mealy bug Maconellicoccus hirsutus (Green) at the Tamil Nadu Agricultural University, Coimbatore.Â The native botanicals such as Andrographis leaf extract, Leucas leaf extract, Neem seed kernel extract, vitex leaf extract, fish oil rosin soap, ocimum leaf extract and lawsonia leaf extract at different dose levels viz., 1, 2, 4, 8 and 10 per cent respectively. After 48 Hor (Hour of release) the highest repellency was recorded in case of Andrographis leaf extract (99.0%) followed by Leucas leaf extract and NSKE (99.0%). Vitex leaf extract and FORS showed on par results among various treatments. The ocimum leaf extract (90.1%) also recorded a moderate repellent effect and the least repellency was recorded in case of Lawsonia leaf extract (81.3%). Similar trend was recorded during 24 hour of release also. As the dose increases the repellent effect also increased irrespective of the native botanical extracts against mealy bugs. <span style="font-family: ";Arial Narrow";,";sans-serif";; letter-spacing: -0.2pt; font-size: 12pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">